Impact of HR Practices on Intention to Quit in Hotel Industry - Singh, Neeraj Shailli; Sharma, Archana; Seth, Manisha; Bahadur, Shefali (International Review of Management and Marketing, 2025)
High turnover rates continue to be a major challenge in the hotel sector, significantly impacting service quality and operational efficiency. This study explores how human resource (HR) policies influence employee turnover by identifying key HR practices that affect employee’s decisions to leave their jobs. The research aims to analyse the impact of various HR practices, including remuneration and benefits, training and development, work-life balance, job security, and employee engagement, on employee retention. By understanding these factors, the study seeks to highlight areas where HR policy reforms can help reduce attrition rates. A structured quantitative approach was employed to collect primary data through surveys conducted with hotel sector employees. The data was analyzed using linear regression modelling to evaluate the relationship between HR policies and employee turnover. The results indicate that certain HR practices have a statistically significant impact on employees’ intentions to quit. These findings highlight key areas where changes in HR policies could improve employee retention. The study provides valuable insights for hotel managers and HR professionals, offering data-driven recommendations to reduce turnover and build a more stable workforce.